PENGENDALIAN HAMA PENGGEREK BATANG CENGKIH (Hexamitodera semivelutina Hell.) MENGGUNAKAN INSEKTISIDA FIPRONIL DAN EMAMEKTIN BENZOAT DENGAN METODE INJEKSI LUBANG PADA BATANG - Trisakti M. C. Manengkey; Elisabeth R.M. Meray; Caroulus S. Rante (COCOS, 2022)
ABSTRACT This study aims to determine the effectiveness of the use of insecticides fipronil and emamectin benzoate by injection of stem holes in clove plants againstlarvae H. semivelutina. The results are expected to provide benefits for farmers in controllingpests H. semivelutina with fipronil and emamectin benzoate insecticides on clove plants by injection of holes in the stems. The research was conducted in a clove plantation area owned by farmers in Talaitad Village, Suluun Tareran District, South Minahasa Regency, North Sulawesi Province. The study lasted for 3 (three) months, from April to June 2021. This study used the Completely Randomized Design (CRD) method on clove plants belonging to farmers. Determination of plants to be applied to injection holes in the stem is done by looking at plants that are attacked bypests H. semivelutina by looking at the hoist holes that secrete liquid mixed with dirt on the clove plant. The results showed that the percentage of the effectiveness of the insecticide fipronil was 56%, which was not significantly different from that of emamectin benzoate, which was 40%, but was significantly different from the control by 0%. This study concluded that the use of fipronil and emamectin benzoate insecticides in the clove plantation area in Talaitad Village, South Minahasa Regency had a high enough killing power in controlling the clove stem borer H. semivelutina. The effectiveness of the application of Fipronil insecticide is 56% and Emamectin benzoate insecticide is 40% and as for suggestions in this study the use of Fipronil and Emamectin Benzoate insecticides is one way to control the pest population of H. semivelutina, besides that there are also various control methods that can be combined by using insecticides. However, its use must also be in accordance with the recommendations so as to reduce the occurrence of pollution and negative impacts on plants and the environment. Keywords : Effectiveness, Emamectin Benzoate, Fipronil, H. semivelutina.